2012
DOI: 10.7763/ijcee.2012.v4.462
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Magnetic Suspension System with a Three-degree-of-freedom Using RBF Neural Network Controller

Abstract: Abstract-In this paper an intelligent method is proposed for controlling a kind of magnetic suspension system with 3 degree of freedom. At first, the dynamic of the magnetic suspension system and the related equations are presented. Regarding unstable nature and non-linearity of magnetic suspension system using techniques of liner control for achieving optimal performance so that all requirements of system are met in all domains is difficult. Then optimal controlling input for magnetic suspension system is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“… average levitation (AL) -performances are similar with performances obtained from three control logics (Section II),  stabilized levitation (SL) -one position levitation performances were improved (obtained in [15]),  no levitation state (NLS) -levitation of the ball was not performed,  levitation with motions (LWM) -two position levitation was obtained.…”
Section: Newly Developed Neural Network and Experimental Resultssupporting
confidence: 53%
See 1 more Smart Citation
“… average levitation (AL) -performances are similar with performances obtained from three control logics (Section II),  stabilized levitation (SL) -one position levitation performances were improved (obtained in [15]),  no levitation state (NLS) -levitation of the ball was not performed,  levitation with motions (LWM) -two position levitation was obtained.…”
Section: Newly Developed Neural Network and Experimental Resultssupporting
confidence: 53%
“…Usage of a feedforward network with one hidden layer in levitation control logic is presented in [14]. An intelligent method is proposed for controlling three degrees of freedom of magnetic suspension system in [15]. Educational paper [16] describes a real-time digital control environment with a magnetic levitation device usage, optimized for neural network implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of node m at node n has the probability P Y mn (t), as shown in (18). This relation is used by the ants, for complete construction of the solution, in each generation of the algorithm.…”
Section: A Ant Colony Optimization (Aco)mentioning
confidence: 99%
“…Experiments performed on a system with predefined control signals has shown that the levitation amplitude of the designated levitation object upon surpassing 10 −4 m doesn't provide sustainable double levitation. The neural network has been developed on the basis of standard sigmoid and tangent functions by utilizing the real observational evidence [18]- [22]. Default activation functions were replaced with new orthogonal polynomial functions [23]- [25].…”
Section: Introductionmentioning
confidence: 99%
“…By the characteristic of open loop instability concerned to magnetic levitation systems, it is essential the development of efficient controllers to manipulate the position of objects under this situation, influencing the safeness and comfort of the passengers using a transportation under this working principle [5].…”
Section: Introductionmentioning
confidence: 99%